2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944315
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic tension EMG to characterize the effects of DBS treatment of advanced Parkinson's disease

Abstract: Deep brain stimulation (DBS) is an effective treatment method for motor symptoms of advanced Parkinson's disease. DBS-electrode is implanted to subthalamic nucleus to give precisely allocated electrical stimuli to brain. The optimal stimulus type has to be adjusted individually. Disease severity, main symptoms and biological factors play a role in correctly setting up the device. Currently there are no objective methods to assess the efficacy of DBS, hence the adjustment is based solely on clinical assessment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…However, to our knowledge, only five studies have investigated sEMG biomarkers for quantifying the efficacy of DBS, as described in previous studies (12,17,36,38). In line with previous studies, our results confirmed that sEMG features were sufficiently robust and sensitive to quantify the efficacy of DBS via three sEMG biomarkers: Peak(f)PSD, wRMS, and MNP.…”
Section: Semg Biomarkers For Dbssupporting
confidence: 90%
See 1 more Smart Citation
“…However, to our knowledge, only five studies have investigated sEMG biomarkers for quantifying the efficacy of DBS, as described in previous studies (12,17,36,38). In line with previous studies, our results confirmed that sEMG features were sufficiently robust and sensitive to quantify the efficacy of DBS via three sEMG biomarkers: Peak(f)PSD, wRMS, and MNP.…”
Section: Semg Biomarkers For Dbssupporting
confidence: 90%
“…In the past few years, sEMG has been proposed to discriminate patients from normal controls (14,33). It was also used to distinguish between essential tremor and tremor of PD through spectrally based methods, such as amplitude analysis (14), wavelet-based approaches (34,35), linear and non-linear parameters (33,36), EMG-burst shape analysis (36,37), and a principal component approach (12).…”
Section: Semg Biomarkers For Dbsmentioning
confidence: 99%
“…These signals give an idea of the neuromuscular activity associated with a contraction, but does not necessarily indicates the force developed by the muscle, instead it gives the information of which muscle was activated by the central nervous system and which muscle provides indirectly a more leading role in a function or movement particularly [6]. EMG signals are used in the medical field for diagnosing muscle diseases such as myopathy, neuropathy [11] or Parkinson's disease [12] and, thanks to technological advances these signals are also used as control signals for electronic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, muscle activity tests are available only in the hospital environment. The analysis of the muscle activity is reported in some recent studies concerning PD ( 12 14 ). The authors in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The authors in Ref. ( 12 , 13 ) particularly observe the muscles’ behavior during deep brain stimulation. They report that Parkinson’s disease symptoms change the EMG signal properties and suggest that EMG analysis is able to detect differences between the deep brain stimulation settings.…”
Section: Introductionmentioning
confidence: 99%